Finite element analysis of thermal stress intensity factors for cracked bimaterial system under convective cooling - Ali, Arafath; Hrairi, Meftah; Mohamed Ali, Jaffar Syed (2018)
Edge-crack bi material systems subjected to convective cooling is considered. The medium is assumed to be insulated on one surface and exposed to sudden convective cooling on another surface containing the edge crack. Superposition and uncoupled quasi-static thermo elasticity principles are adopted to find temperature and thermal stress distribution. The ANSYS results for the stress intensity factors of an edge crack are calculated and presented as a function of time, crack length, and thickness ratio for two different bimaterial systems, namely a stainless steel layer welded on ferritic steel and a ceramic layer coating on ferric steel